Community nurses’ knowledge and nursing care skills on enteral nutrition: a knowledge transfer program - Mohamed Ludin, Salizar; Mohd Nor Rudin, Noriedayu; Makhtar, Aniawanis (Elsevier Espana, S.L.U., 2021)
The researcher aims to evaluate the effect of the knowledge transfer program on community nurses’ knowledge and nursing care skills on enteral nutrition in the care of critically ill survivors. In this study, the researcher used an interventional study; a pre-test and post-test for community nurses’ knowledge of enteral nutrition and a post-test for nursing care skills on enteral nutrition. This program involved community nurses currently working at community clinics under the Ministry of Health Malaysia. Pre- and post-test community nurses’ knowledge of the knowledge transfer program shows an improvement result. There was no association between the knowledge of community nurses and nursing care skills on enteral nutrition. Knowledge transfer program enhanced community nurses’ knowledge and nursing care skills on enteral nutrition care for critically ill survivors in community settings.